Alberta's Occupational Health and Safety Amendment Act, 1983 - Fisher, E.G.; Ivankovich, I.F. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This paper presents and analyses the salient features of the 1983 amendments enacted by Alberta's Progressive Conservative Government.